Socio-ecological approach in floodswamp management for fish conservation - Khusnul Khotimah; Muslim Muslim; Daniel Saputra; Ferdinand Hukama Taqwa (Acta Aquatica: Aquatic Sciences Journal, 2026)
Floodplain swamp are seasonally inundated aquatic ecosystems that play vital ecological roles as habitats, spawning grounds, and natural buffers supporting local fish diversity in Indonesia, particularly in South Sumatra. However, pressures from land conversion, environmental degradation, and overexploitation have caused a decline in biodiversity and now threaten the long-term sustainability of these ecosystems. This study employs a Systematic Literature Review (SLR) approach, guided by the PRISMA protocol, to explore the role of socio-ecological approaches in managing floodplain swamp for fish conservation. The analysis was conducted through thematic and bibliometric synthesis using VOSviewer software to identify research trends, thematic clusters, and existing knowledge gaps. The findings reveal that the success of fish conservation in floodplain swamp depends not only on ecological factors but also on social, cultural, economic, and institutional dimensions. Integrating local wisdom such as the Lubuk Larangan system and traditional fisheries regulations with modern scientific frameworks like Adaptive Collaborative Management enhances socio ecological resilience and conservation effectiveness. An adaptive and participatory socio ecological management model for floodplain swamp is therefore essential to ensure the sustainability of fish resources and the well-being of local communities. Keywords: Conservation; Floodplain Swamp; Local Wisdom; Socio-Ecology